The Severity of COVID-19 in Patients with Hematological and Solid Malignancies: a Sample from Medical City in Baghdad. - Abdul Hussein, Zahra A.; AL-Obaidy, Muhammed W.; Hashim, Tahseen M.; Al-Khairalla, Mudher (Journal of the Faculty of Medicine Baghdad, 2024)
Background: A novel virus known as severe known as severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) primarily targets the respiratory system of infected people. The virus spreads between individuals through respiratory droplets produced during sneezing or coughing. Anyone can contract the virus, but the severity of the disease is often associated with age and pre-existing medical conditions like cancer that may weaken the immune system.Objectives: In this study, we analyzed severe outcomes of SARS-CoV-2 infections among patients with current or prior malignancy.Patients and Methods: Between January 1st and December 31st, 2021, a cross-sectional study was conducted on 100 cancer patients from various medical centers in Baghdad, Iraq. The patients included 50% with solid tumors and 50% with hematologic malignancies. The medical centers involved in the study were the Oncology Teaching Hospital, Baghdad Hematological Center, and Private Nursing Home Hospital in the Medical City Complex. The patients were infected with severe acute respiratory syndrome coronavirus 2.Results: There is a significant correlation between the severity of COVID-19 in cancer patients and their Eastern Cooperative Oncology Group (ECOG) performance status score of ≥1 (10%, P=0.009), the duration of their malignancy being ≥3 years (30%, P=0.017), and the status of their cancer at the time of COVID-19 infection, with patients having was found malignant disease being more likely to develop critical cases. Additionally, patients in remission during their coronavirus infection were found to have developed more critical cases (80%, P=0.001), which was statistically approved.Conclusion: We found that COVID-19 severity parameters, rather than the underlying malignant disease, are the primary factors in morbidity and mortality